THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, WORK DISCIPLINE ON PERFORMANCE OF PT. EMPLOYEES. JASA MARGA (PERSERO). Tbk BELMERA MEDAN BRANCH - Agnes Pratiwi Br Damanik; Andre Fitriano; Dina Eldina Marbun; Ellin; Bambang Sutejo (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to explain the influence of Organizational Culture, Work Environment, Work Discipline on Employee Performance at PT. Jasa Marga (Persero) Tbk. Belmera Medan Branch. The population of this study was 152 and the sample was calculated using the Slovin formula to obtain results of 61 respondents. The method in this research is a quantitative method. The data collection techniques used were interviews, documentation studies and questionnaires. For data analysis techniques in this research using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, F tests, T tests, and coefficient of determination tests (R2) using SPSS version 25. Based on the research results, it shows that the test results t the Organizational Culture variable (X1) has a partially significant effect on employee performance, the Work Environment (X2) has no partial significant effect on employee performance, and Work Discipline (X3) has a partially significant effect on employee performance. The results of the F test show that Organizational Culture, Work Environment, Work Discipline have a positive and significant effect simultaneously on PT Employee Performance. Jasa Marga (Persero) Tbk. Belmera Medan Branch with a sig value of 0.000<0.05.